Determinants of waste separation behavior Tabriz, Iran: An application of the theory of planned behavior at health center - Babazadeh, Towhid; Ranjbaran, Soheila; Kouzekanani, Kamiar; Abedi Nerbin, Sanaz; Heizomi, Haleh; Ramazani, Mohammad Ebrahim (Frontiers in Environmental Science, 2023)
Background: Identifying factors that may influencing waste separation behavior can lead to more effective separating and recycling plans in a community. The primary purpose of the survey was to identify the key factors of such behavior. Methods: The scientific inquiry was cross-sectional in nature, took place in Tabriz, Iran, and employed multistage random sampling to recruit the study’s 360 participants. A Theory of Planned Behavior-driven questionnaire was developed by the research team for the purpose of data collection. Results: Structural equation modeling of the data showed that source separation intention was positively influenced by higher perceived behavioral control, moral commitments, and perceived policies effectiveness, while intention and perceived behavioral control were useful in predicting waste separation behaviors. Conclusions: Recycling investors and other stakeholders should focus on perceived behavioral control and intention in designing and implementing waste separation programs.